G340(P) Ethosuximide Retention in Children with Epilepsy. (7th April 2014) - Pickerd, N; Gale, K; Hartley, L; Gibbon, F; te WaterNaude, J
Abstract : Ethosuximide is recommended as first line treatment for childhood absence epilepsy (CAE) 1 . It has been found to be more effective than Lamotrigine and to have fewer side effects than Lamotrigine and Valproate 2 . Objective: The aim of this study was to assess the efficacy and tolerability of Ethosuximide in children. Methods: The notes of all patients attending a tertiary Paediatric Neurology clinic who were prescribed Ethosuximide over a 5 year period (January 2008 to January 2013) were requested. The duration of treatment with Ethosuximide, the reason for discontinuation and any side effects were recorded. Results: Fifty-three patients were prescribed Ethosuximide. Notes could be retrieved in 51 patients and sufficient detail about the treatment with Ethosuximide was available in 46, 25 of them female. In 22/46 (48%) Ethosuximide was prescribed for CAE; in the remaining it was used as an add-on drug for other epilepsies. The mean age at commencing treatment was 8..1 years. The median duration of treatment with Ethosuximide was 6 months (range 171 months). Thirty-four children (74%) discontinued treatment with Ethosuximide, 18 because of treatment failure, 10 due to side effects and in 6 patients both. The commonest side effects were vomiting and abdominal pain; worsening behaviour, nightmares, rashes and drowsiness were also encountered. In CAE it was discontinued in 8/22 (36%) because of a lack of efficacy, and 6/22 (27%) because of side-effects. Conclusion: The usefulness of Ethosuximide in treating epilepsy in this group of patients is limited by its efficacy and tolerability. This differs from the good retention and side-effect profile reported for this anticonvulsant drug (AED). It might be worth reviewing these findings on a larger scale to define this more precisely, as our experience with this AED would suggest that it has a limited utility as a first-line agent. References: NICE clinical guideline 137, The epilepsies: the diagnosis and management of the epilepsies in adults and children in primary and secondary care, Issued: January 2012 Glauser TA, Cnaan A, Shinnar S et al ., Ethosuximide, Valproic Acid, and Lamotrigine in Childhood Absence Epilepsy, N Engl J Med 2010;362:790–9.